The Agenda of the Day: A Study about the Brazilian Congress in Editorials of Folha de S. Paulo and O Estado de S. Paulo - Mont’Alverne, Camila; Marques, Francisco Paulo Jamil (Brazilian journalism research, 2016)
In order to update the debate about journalism and agenda-setting, the article examines the main issues discussed by Folha de S. Paulo and O Estado de S. Paulo in their editorials. By using Content Analysis, we analyze 164 texts published by both newspapers between 2011 and 2013. All editorials in our sample mention the terms “Brazilian Congress”, “Senate” or “Brazilian House of Representatives”. Our results point that, among the issues considered of relevance by the newspapers, there are relations between the government and its allies in Congress and political scandals; other issues of social interest were also addressed by the editorials, such as labor legislation and the quality of education and health services. The fact that editorial is an institutional genre gives a special relevance to the agendas adopted by it. The diverse emphases verified in OESP and FSP editorials also highlight that journalistic institutions have their own interests. Therefore, it is necessary that the literature deepens the debate about “editorialized criteria”, aiming to understand to which extent journalistic companies not only set some agendas as those that are more important, but also highlight particular political perspectives.